Pengaruh Penerapan PSAK 72 terhadap Kualitas Laporan Keuangan Perusahaan Terbuka: Literature Review - Piter Arson Welay; Bella Sianka Sulistyowati (Media Akuntansi Perpajakan, 2026)
This study is a systematic literature review aiming to synthesize empirical findings on the effect of PSAK 72 implementation on the quality of financial statements of publicly listed companies in Indonesia, focusing on two dimensions: value relevance and earnings management. Employing a qualitative systematic review approach, 15 peer-reviewed articles published between 2020 and 2025 were analyzed. The findings reveal that PSAK 72 improves transparency and comparability but reduces the value relevance of earnings and earnings per share in the property and construction sectors, while earnings management practices do not show significant reduction post-implementation. The impact varies across industrial sectors, with the property sector experiencing the most significant consequences. These findings imply the need for more specific sectoral guidance and enhanced governance mechanisms to maximize the benefits of the new standard.Keywords: PSAK 72, IFRS 15, value relevance, earnings management, systematic literature review.